Quantitative Methods in Participatory Research: Being sensitive to issues of scientific validity, community safety, and the academic-community relationship - Macaulay, Ann; Jagosh, Justin; Pluye, Pierre; Bush, Paula; Salsberg, Jon (Nouvelles pratiques sociales, 2013)
In this paper, we suggest that participatory research (PR) is neither a research methodology, nor uniquely associated with qualitative methods, but rather an approach to research through which stakeholders can implement quantitative, qualitative or mixed methods study designs. By illustrating three partnerships retained in our recent systematic review of PR, we highlight issues involved in partnered quantitative research. Examples demonstrate that commitment to dialogue and consensus building among partnership stakeholders is key to ensuring that methods generate scientifically valid research without creating community harm, loss of reputation, stigma or without generating feelings of denial, betrayal and exclusion.